2017
DOI: 10.18632/oncotarget.19571
|View full text |Cite
|
Sign up to set email alerts
|

Rab25 GTPase: Functional roles in cancer

Abstract: Rab25, a small GTPase belongs to the Rab protein family, has a pivotal role in cancer pathophysiology. Rab25 governs cell-surface receptors recycling and cellular signaling pathways activation, allowing it to control a diverse range of cellular functions, including cell proliferation, cell motility and cell death. Aberrant expression of Rab25 was linked to cancer development. Majority of research findings revealed that Rab25 is an oncogene. Elevated expression of Rab25 was correlated with poor prognosis and ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 68 publications
(131 reference statements)
0
46
0
Order By: Relevance
“…For instance, as it relates to exocytosis and cancer, dysregulation of the class of small GTPases and Rab effector proteins, such as Rab27a and Rab27b isoforms, Rab25, Rab40b, and Rabphilin, has been shown to promote tumor cell migration, invasion, and metastasis through disruption of membrane vesicle trafficking and docking (Gomi et al, 2007;Hendrix et al, 2010b;Shaughnessy and Echard, 2018;Tzeng et al, 2017;Tzeng and Wang, 2016;Wang et al, 2017). The soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein receptors, soluble NSF attachment protein receptor (SNARE) proteins, and SNARE modulators have long been implicated in vesicle trafficking and fusion in synaptic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as it relates to exocytosis and cancer, dysregulation of the class of small GTPases and Rab effector proteins, such as Rab27a and Rab27b isoforms, Rab25, Rab40b, and Rabphilin, has been shown to promote tumor cell migration, invasion, and metastasis through disruption of membrane vesicle trafficking and docking (Gomi et al, 2007;Hendrix et al, 2010b;Shaughnessy and Echard, 2018;Tzeng et al, 2017;Tzeng and Wang, 2016;Wang et al, 2017). The soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein receptors, soluble NSF attachment protein receptor (SNARE) proteins, and SNARE modulators have long been implicated in vesicle trafficking and fusion in synaptic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple clinical findings support the role of Rab25 as a prognostic marker for patients with several types of cancers such as breast, ovarian and renal cancer [47]. Furthermore, Rab25 mRNA is increased in multiple other cancer types including ovarian, prostate, bladder, breast and liver cancers making it a highly relevant target for potential cancer therapies.…”
Section: Rab25mentioning
confidence: 82%
“…It recognizes a conserved motif found in the α-tails of all integrins (apart from α11) and regulates integrin endocytosis (Pellinen et al, 2006;Mai et al, 2011). RAB25, on the other hand, is expressed only in specific epithelial tissues and some carcinomas (Wang et al, 2017) and associates with the fibronectin-binding α5β1-integrin to drive its recycling (Caswell et al, 2007). Previous studies have shown the role of RAB13 in trafficking of receptors between trans-Golgi network and transferrinpositive recycling endosomes in epithelial cells (Nokes et al, 2008) and activation of RAB13 by guanine nucleotide exchange factor DENND2B on the plasma membrane has been linked to cancer cell migration and invasion (Ioannou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%